Onion (Allium cepa L.) Bulb Crop Production Using Sets of Two Sudanese Cultivars (University of Khartoum Journal of Agricultural Sciences, 2021)
The objective of this research was to determine production requirement for onion bulb crop using sets as, rarely but of high potential, planting material. An experiment was carried out at the Demonstration Farm of the Faculty of Agriculture, University of Khartoum for two consecutive growing seasons,(2010/11 and 2011/12). Treatments comprised two cultivars(Saggai and Kamlin), three set sizes (small 1-1.5 cm diameter; medium 1.6- 2.1 cm and large 2.2-2.7 cm) and three planting dates (15th of August, September and October). Treatments were arranged in a split split plot design with three replications, where cultivars were randomized in the main plots, set sizes in the sub-plots and planting dates in the sub-sub plots. Resultsindicated that increasing set size from small to large size significantly promoted plant growth. Medium set size resulted in significantly higher average bulb weight, total and marketable yields than small and large sets; however, bulb splitting and premature bolting (negative quality traits) were also high. So marketable yield represented a range of 40-46 %, 39-49 % and25-53 % of the total yields over the two years when medium, large and small were used respectively. Plant growth, average bulb weight, bulb diameter, total and marketable yields were significantly higher from sets planted inOctober and in September than in August; yet, bolting was also significantly higher. Early planting in August significantly increased bulb dry matter. Saggai cultivar had higher tendency for bolting and splitting than Kamlin when sets were used as planting material. Total and marketable yields were significantly higher from medium sets planted in October and September than in August. It is concluded that use of sets as planting material is as good as transplants, if not better, as it is more easy and adaptable to the continuously changing growing environment in terms of climate change and production cost.
Keywords: Allium cepa L.; onion sets; planting date; onion; premature bolting; bulb splitting